Shaping Entrepreneurial Intention Through Education among Business Undergraduates in an Underdeveloped Economy: Evidence from Yemen - Mugaahed Abdu Kaid Saleh; Manjunath K R (International Journal of Entrepreneurship, Business, and Creative Economy, 2024)
Education plays a significant role in developing entrepreneurial mindset among undergraduate students. However, regarding the aspect of lower income economies, research has not fully paid attention to its exploration. Hence, this study aims to identify the role of entrepreneurial education in shaping entrepreneurial intention among undergraduates in Yemen, an underdeveloped economy. With the help of data collected from 247 students in two universities in Yemen, the results indicate a significant impact of entrepreneurial education on intention among business undergraduates. Further, the results indicate a partial mediation of entrepreneurial attitude and background in the relationship between entrepreneurial education and intention, and no mediating role is observed with entrepreneurial skills in the same relationship. This research adds to the scant literature relevant to underdeveloped economies and therefore could be a useful resource for policy makers to pay more attention to developing entrepreneurial programs focusing on talent and skill development in higher education, which can improve the harmonization between universities and the industrial sector and further entrepreneurship development.